(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Eyngium foetidum L. is a medicinal plant widely used by ethnic tribal communities of Assam as an alternative source of medicine for the treatment of various diseases. The present investigation was undertaken with an aim to isolate, identify and assess the antimicrobial activity of endophytic fungi associated with the healthy leaf tissues of E. foetidum. The endophytic fungi were isolated three different media, namely, Potato Dextrose Agar (PDA), Malt Extract Agar (MEA) and Water Agar (WA) media and from three different sites. Altogether, 84 endophytic fungal isolates were isolated from 150 segments of leaf tissues. Dominant endophytes were found to be fungi belonging to the genus Colletotrichum, followed by non-sporulating members grouped under mycelia sterilia. Other fungal genera that were isolated as endophytes were Scopulariopsis, Cladosporium, Stemphylium, Penicilllium and Alternaria. The endophytic fungi thus isolated were studied for antimicrobial activity against some clinically significant human pathogenic test organisms. Ethyl acetate extracts of all endophytes exhibited antimicrobial activity by inhibiting at least one out of all the test pathogens. Amongst the isolated fungi, extracts obtained from three endophytes showed wide-spectrum activity against all the test organisms. The fungal endophytes were identified as Scopulariopsis sp., Penicillium sp. and a sterile isolate morphotype strain EF6. The study indicated that E. foetidum harbours a wide range of endophytes with antimicrobial properties and further detailed investigation of the compound present in them would lead to their potential therapeutic applications as a new source of medicine.